"A nice white lady": critical whiteness studies, teacher education, and city schools. Issue 7 (9th August 2022) - Wozolek, Boni; Atif, Ameena
Abstract: Critical Whiteness Studies (CWS) can be a significant tool to dismantle white supremacy in educational contexts. However, the authors argue that without attending to the forms of curriculum as they are entangled across systems of schooling, CWS can reinscribe the very forms of whiteness it seeks to disrupt. Identifying as a queer, Brown assistant professor of education and a Black undergraduate student who recently finished her studies, this paper uses a duo-ethnographic approach to examine what the authors call an "enacted curriculum of whiteness." Through their respective narratives, the authors explore how students and faculty bracketed CWS, often identifying CWS as a part of the formal curriculum while using the enacted curriculum to defend and maintain normalized racism. The authors argue that alongside CWS in teacher preparation, an emphasis on curriculum studies is critical to resisting the "nice white lady" phenomenon that often infects teacher preparation and, eventually, K-12 schools.